Bring me home! : - Bonham, Margaret H. (Wiley Pub., 2005)
The book to bring home before you bring home a puppy or a dog! Dogs are wonderful companions, but they need lots of attention and care. Are you up for the challenge? With this practical, hands-on guide, you'll know what to expect—cost-wise, care-wise, and chore-wise. You'll have information on choosing the right dog for your family, caring for it, and more. Information and interactive activities include: Worksheets that help you make informed decisions, choose a breeder or a veterinarian, and more Questions and charts to help you determine if your family is ready for dog ownership, whether to get a puppy or a dog, and more Checklists covering how to puppy-proof a home, vaccinations your pet should have, items you'll need before bringing the bundle of joy home, and other aspects of being a responsible pet "parent"